SLUP: A Standard List of Usability Problems in Multimodal Video Games designed for People Who Are Blind - Darin, Ticianne; Andrade, Rossana; Sánchez, Jaime (Anais Estendidos do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC); 2018: Anais Estendidos do XVII Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais, 2018)
This paper summarizes the proposal and validation of the Standard List of Usability Problems (SLUP), a categorized list of typical problems affecting the interaction of people who are blind with audio- and haptic-based multimodal video games. SLUP can help designers to avoid recurrent usability issues in the design of multimodal games for users who are blind. Besides, evidence decurrent from user tests showed that SLUP may be further expanded and used as a ground to develop specific usability evaluation instruments.